Evaluation of patients in need of continuous care based on a case series - Erkman, Fatma tuğba; Balseven Odabaşı, Aysun; Tümer, Ali Rıza; Akçan, Ramazan; Cavlak, Mehmet (The Bulletin of Legal Medicine, 2025)
The condition of being permanently dependent on care refers to the continuous need for assistance from another person in order to perform basic and instrumental activities of daily living (e.g., eating, personal hygiene, bathing, toileting, dressing, etc.). In our country, there is no widely accepted and commonly used scale for evaluating the need for permanent care by another person. This study aims to demonstrate the utility of employing the Barthel Index of Activities of Daily Living (BI-ADL) and the Functional Independence Measure (FIM) in assessing patients who are claimed to require permanent care, through the evaluation of specific cases.In this study, 89 cases who applied for disability evaluation following traffic accidents and were assessed to have a disability rate of 70% or above were examined. Reports indicating permanent care dependency were issued in 57 of these cases. However, it was determined that 25 of these (44%) did...
Keywords: constant need for care; Disability; daily living activities